Effect of Vermicompost in Propagation of Mycorrhizal (Glomus sp) Post-Coal Mining Land with Cereal Host Plant - Prasetya, Budi; Widagdo, Bachtiar Dio; Tuheteru, Faisal Danu (Asosiasi Mikoriza Indonesia, 2024)
The composition of host plant species and nutrient sources affects the success of mycorrhizal (Glomus sp) propagation in post-coal mining land. Plants that can be used as alternative hosts are cereals such as corn, millet, and sorghum. Vermicompost is an alternative source of nutrients to supply the nutrient needs of post-coal mining soil media. This study aimed to analyze the addition of vermicompost, the effect of different host plants, and the combination of both in the propagation of Glomus sp. The study was conducted in a greenhouse using a factorial completely randomized design with the first factor being the host plant and the second factor being the dose of vermicompost. The results showed that the addition of vermicompost increased the number of spores and the percentage of mycorrhizae colonization on the roots of each host plant with optimum yield. The combination dose of vermicompost (2 g pot-1) and millet as a host plant produced the highest number of spores of 4,880 spores pot-1 with root colonization reaching to 63.3%